2006
DOI: 10.1074/jbc.m606151200
|View full text |Cite
|
Sign up to set email alerts
|

Laminin 5 Regulates Polycystic Kidney Cell Proliferation and Cyst Formation

Abstract: Renal cyst formation is the hallmark of autosomal dominant polycystic kidney disease (ADPKD). ADPKD cyst-lining cells have an increased proliferation rate and are surrounded by an abnormal extracellular matrix (ECM). We have previously shown that Laminin 5 (Ln-5, a ␣ 3 ␤ 3 ␥ 2 trimer) is aberrantly expressed in the pericystic ECM of ADPKD kidneys. We report that ADPKD cells in primary cultures produce and secrete Ln-5 that is incorporated to the pericystic ECM in an in vitro model of cystogenesis. In monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…9 On the contrary, a proliferative activity of Ln-5 has recently been proposed in a developmental disorder and confirmed in HCC. 26 These results explain why Iressa, an EGFR inhibitor currently used in clinical trials, lacks an antiproliferative effect on the same HCC cell lines used here, in presence of Ln-5. 27 The possibility that Ln-5 phosphorylates EGFR thanks to the DIII domain generated by proteolytic cleavage by matrix metalloproteinases has been proposed, but does not seem to be the case in our experimental conditions, since EGF phosphorylates EGFR but Ln-5 does not.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…9 On the contrary, a proliferative activity of Ln-5 has recently been proposed in a developmental disorder and confirmed in HCC. 26 These results explain why Iressa, an EGFR inhibitor currently used in clinical trials, lacks an antiproliferative effect on the same HCC cell lines used here, in presence of Ln-5. 27 The possibility that Ln-5 phosphorylates EGFR thanks to the DIII domain generated by proteolytic cleavage by matrix metalloproteinases has been proposed, but does not seem to be the case in our experimental conditions, since EGF phosphorylates EGFR but Ln-5 does not.…”
Section: Discussionsupporting
confidence: 57%
“…28 In our experimental model, the proliferative effect is mediated by Erk, as also reported in the case of polycystic kidney cells. 26 However, in their case Erk was phosphorylated as a consequence of ␤4 integrin subunit activation, as previously suggested. 26, 29 The role of ␤4 in cell proliferation is also demonstrated by the fact that ␤4 mutated keratinocytes do not proliferate in the presence of Ln-5, and Erk remains confined to the cytoplasm rather than being translocated into the nucleus.…”
Section: Discussionmentioning
confidence: 57%
“…For example, the polarized deposition of laminin is needed for the transition of mesenchyme to polarized epithelial cells during mouse kidney development (Sorokin et al, 1990). Also, laminin contributes to the cystotubulogenesis of kidney epithelium (Klein et al, 1988) and regulates the cystogenesis of polycystic kidney cells (Joly et al, 2006). MDCK epithelial cells are derived from canine renal tubular epithelium (Simons and Fuller, 1985) and have been commonly used for in vitro studies of epithelial structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using real-time PCR studies performed on the RNA extracted from primary cultures of the cystic epithelia derived from ADPKD kidneys as well as from PKD kidney tissues, they confirmed the abnormal expression of integrin 4 and laminin 2 in ADPKD. The same authors presented a more rigorous study on the role of abnormal expression of laminin-332 in ADPKD cystogenesis (Joly et al, 2006). They demonstrated that ADPKD primary cultures synthesized and secreted laminin-332 which was then incorporated into the ECM of cysts that developed in matrigel cultures of these cells.…”
Section: Recent Studiesmentioning
confidence: 99%